Benzyl N0-[1-(3-pyridyl)ethylidene]-hydrazinecarbodithioate - How, Fiona Ni Foong; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
The title compound, C15H5N2S2, crystallizes as a trans–cis conformer. The thione sulfur is in a trans position with the methyl pyridyl fragment with respect to the C—N bond but adopts a cis position with the benzyl ring across the C—S bond. The dihedral angle between the planar quinoline ring and the dithiocarbazate unit is 103.70 (1). The inclination of the dithiocarbazate unit with the benzyl group is 17.20 (1).There are strong – stacking interactions between pairs of dithiocarbazate units and also pairs of pyridine rings [3.27 (5)and 3.28 (5) A ° , respectively]. A long-distance intermolecular N—H N hydrogen bond [3.171 (2) A ° ] also stabilizes the structure.